Postoperative Course of Pars Flaccida Cholesteatoma Patients With Habitual Sniffing. Issue 10 (December 2020) - Endo, Shiori; Mizuta, Kunihiro; Takahashi, Goro; Arai, Maki; Nakanishi, Hiroshi; Takizawa, Yoshinori; Hosokawa, Kumiko; Yamatodani, Takashi; Misawa, Kiyoshi; Hosokawa, Seiji; Mineta, Hiroyuki
Abstract : Objective: To investigate the effects of habitual sniffing on the postoperative course of pars flaccida cholesteatoma. Study Design: Retrospective case series study. Setting: University hospital. Patients: Forty-nine patients (53 ears) with pars flaccida cholesteatoma and history of habitual sniffing before the initial operation. Interventions: Patients were divided into a "sniffing cessation group" characterized by sniffing cessation and a "continual sniffing group" characterized by continuation of sniffing despite instructions for conscious cessation. Main Outcome Measures: Hearing level, tympanic membrane findings, tympanograms, mastoid cell development before the operation, and pneumatization 1 year postoperatively. Results: The sniffing cessation and continual sniffing groups comprised 35 patients (38 ears) and 14 patients (15 ears), respectively. The average postoperative hearing was slightly better in the continual sniffing group. In the sniffing cessation group, retractions were evident in significantly fewer cases. Retractions were observed in all continual sniffing group cases, with a high percentage of severe retractions, wherein the bottom was not visible. Type A tympanogram was predominant in the sniffing cessation group. Mastoid cell development was not significantly different between the two groups. Satisfactory pneumatization was significantly more common in the sniffing cessation group (Fisher's exact test, ** p  < 0.005). Conclusion: Conscious cessation of the sniffing habit could reduce the risk of postoperative retraction and improve pneumatization in patients with pars flaccida cholesteatoma. The presence or absence of the sniffing habit after surgery is a defining factor in postoperative prognosis (retraction, recurrence), and may be a determinant for decisions regarding surgical approach.